Five interpolations in latin poetry - John Trappes Lomax (Exemplaria Classica, 2014)
It is suggested that there have been interpolations of one or more lines at Hor. epist. 1.7.20, iuv. 3.260-1, lucan. 2.605-7, verg. Aen. 9.579; and that there has been interpolation of a single word to restore metre at prop. 2.13.48.